Impact of size and location of metastases on early tumor shrinkage and depth of response in patients with metastatic colorectal cancer: subgroup findings of the randomized, open-label phase 3 trial FIRE-3/AIO KRK-0306 - Froelich, Matthias F.; Petersen, Elina L.; Heinemann, Volker; Nörenberg, Dominik; Hesse, Nina; Gesenhues, Alena B.; Modest, Dominik P.; Sommer, Wieland H.; Hofmann, Felix O.; Stintzing, Sebastian; Holch, Julian W. (Clinical colorectal cancer, 2020)
Background - The Response Evaluation Criteria in Solid Tumors (RECIST) are used to define degrees of response to chemotherapy. For accelerated response evaluation, early tumor shrinkage (ETS) of ≥ 20% has been suggested as a predictor for outcome in metastatic colorectal cancer (mCRC). Together with depth of response (DpR), new alternative metrics have been provided, yielding promising outcome parameters. In this analysis, we aimed to further characterize ETS and DpR. - Patients and Methods - This analysis was based on FIRE-3, a randomized phase 3 trial comparing first-line FOLFIRI plus either cetuximab or bevacizumab in KRAS exon 2 wild-type mCRC. ETS and DpR were determined on the basis of RECIST 1.1 in a blinded radiologic review. ETS was evaluated as a categorized (≥ 20% shrinkage) and continuous parameter. The impact of baseline location and size of metastases on ETS and DpR were evaluated by univariate and multivariate analyses. - Results - Of 592 patients, 395 (66.7%) had data available for radiologic review. Median continuous ETS for lung, liver, and suspected lymph node metastases was 20%, 23%, and 30%, respectively. The median DpR was −32%, −44%, and −50%, respectively (all P < .01). In multivariate analysis, lung metastases were significantly associated with inferior DpR (P = .021), whereas hepatic metastases led to higher DpR (P = .024). Large metastases were associated with favorable ETS, whereas small metastases were correlated with higher DpR (P < .001). - Conclusion - ETS and DpR depend on the location and size of metastases in mCRC. These associations may establish the basis for further research to optimize the predictive accuracy of both parameters. This may help basing treatment decisions on ETS and DpR.
Gesehen am 19.07.2024